Longer school days, less teenage mothers : evidence from Colombia (2017)
This study analyzes the impact of longer school days on teenage fertility. Using administrative data of school enrollment and a national system of beneficiaries for social programs (Sisbén), I am able to identify teenagers who attended a Full School Day (7-hour schedule) or a half-day (4-hour schedule), and whether these teenagers gave birth between 2006 and 2009. I exploit plausibly exogenous within-school variation in the type of school day and estimate panel regressions with school and student fixed effects. Results indicate that attending a full-day instead of a half-day reduces teenage fertility rates by 0.6 p.p. (a 25% reduction from the mean), and that this effect is only evident in urban schools. Also, more years spent in FSD increasingly reduced teenage fertility.